Природно-заповідний фонд Українських Карпат - Петрова, Л.; Третяк, П. (Праці наукового товариства ім. Шевченка, 2003)
У межах фізико-географічних областей реґіону охарактеризована територіяльна і категоріяльна структура мережі об’єктів природно-заповідного фонду. Запропоновано напрями її ландшафтно-географічної і ценотичної оптимізації. With in bounds of a physiographic province the Ukrainian Carpathian mountains reserved
objects occupy 13% of the area. However landscapes of individual physiographic regions are
protected in reserves on the unequal relative areas. On the minimal areas unique landscapes of
Prykarpattia, Volcanic Carpathian Mountains and the Zakarpattia lowland are protected. The
regional network of forest-reserved objects should be optimised: to increase geographical and
coenotycal representativeness. The special reserved regime is necessary for forest-reserved
territories. It is necessary to specify structure of categories of reserves and their purpose.